Fatty acid profile and nutrient composition of muscle and adipose tissue from Malpura and fat-tailed Dumba sheep - BHATT, R S; SONI, LALIT; GADEKAR, Y P; SAHOO, A; SARKAR, SROBANA; KUMAR, DAVENDRA (The Indian Journal of Animal Sciences, 2020)
Fatty acid (FA) profile and nutrient composition of Longissimus dorsi (LD) muscle and various adipose tissues of adult Malpura sheep (4–6 years) and lambs (6 month), and fat tailed Dumba sheep (1 year) were evaluated. Compared to lamb, LD muscle of adult Malpura sheep had lower polyunsaturated FA (PUFA), ω-6, ω-6/ω-3, desirable FA (DFA) and higher atherogenic index (AI), monounsaturated FA (MUFA), ω-3, MUFA:PUFA ratio, short-chain FA (SCFA) and conjugated linoleic acid (CLA). Similarly, adipose tissue fat had higher MUFA, MUFA:PUFA ratio and AI in adult than the lamb. Dumba sheep showed a different FA profile with higher SFA in caul fat and lower in LD muscle, while proportionally lower PUFA in caul fat and higher in LD muscle. Likewise, ω-3 and ω-6 FA was comparatively more in LD muscle while c911 CLA was highest in the tail adipose tissue. Between Malpura and Dumba, the FA profile of LD muscle revealed higher SFA and cis-9 trans-11 CLA but lower PUFA and ω-6 FA in Malpura. It can thus be concluded that Malpura lamb meat is healthier having improved PUFA,ω-6:ω-3 ratio and AI than the adult. Furthermore, Dumba may also be considered a promising mutton breed with significant PUFA, ω-3 and ω-6 FA. Further studies are needed to ascertain the effects of different dietary regime on the FA profile of Dumba and Malpura sheep.